PELATIHAN PENGGUNAAN DAN PEMANFAATAN PAUDPEDIA UNTUK PENGEMBANGAN LITERASI DIGITAL GURU DI KABUPATEN PASURUAN - Kartika Rinakit Adhe; Nurhenti Dorlina Simantupang; Sri Widayati; Nenny Chanidatus Shofiyah (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2022)
Digital literacy is one of the means of supporting the implementation of learning in the application of the independent learning curriculum. This is an effort to recover or recover from learning loss as a result of the Covid-19 pandemic. Improving digital literacy in teachers is expected to be able to optimize the learning process for children. There is a need for training in the use of current technology. The purpose of this study is to describe and explain the use of PAUDPEDIA applications for teachers. As well as improving teacher digital literacy through the use and utilization of PAUDPEDIA. The methods used in this training activity are (1) discussions or lectures; (2) direct guidance/demonstration; and (3) assignment. The results of this training show the enthusiasm of participants in participating in a series of events in the research carried out, this can be seen from the majority of participants who are active and participate in activities from beginning to end.